2016
DOI: 10.2337/dc15-2849
|View full text |Cite
|
Sign up to set email alerts
|

Elevations in the Fasting Serum Proinsulin–to–C-Peptide Ratio Precede the Onset of Type 1 Diabetes

Abstract: OBJECTIVEWe tested whether an elevation in the serum proinsulin–to–C-peptide ratio (PI:C), a biomarker of β-cell endoplasmic reticulum (ER) dysfunction, was associated with progression to type 1 diabetes.RESEARCH DESIGN AND METHODSFasting total PI and C levels were measured in banked serum samples obtained from TrialNet Pathway to Prevention (PTP) participants, a cohort of autoantibody-positive relatives without diabetes of individuals with type 1 diabetes. Samples were obtained ∼12 months before diabetes onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 36 publications
(47 reference statements)
8
91
0
5
Order By: Relevance
“…Based on these findings, Figure 1 illustrates two theoretical patterns of β cell destruction: insulitis may begin early, with destruction proceeding in a semi-linear fashion; or insulitis and β cell destruction may occur closer to diagnosis. The latter fits the observations that (i) the proportion of infiltrated islets is modest near diagnosis, and insulitis is only present in non-diabetic donors with multiple autoantibodies (16,21,23); (ii) β cell loss near diagnosis is partial in many patients (16,21,23), and no appreciable reduction in β cell mass has been reported in autoantibody-positive donors (44,45); and (iii) impaired glucose metabolism, abnormalities of insulin secretion (46,47) and insulin sensitivity (48), and increased β cell death (49) usually manifest shortly before diagnosis in longitudinal studies of at-risk relatives.…”
Section: T Cells In the Prediabetic Pancreassupporting
confidence: 64%
“…Based on these findings, Figure 1 illustrates two theoretical patterns of β cell destruction: insulitis may begin early, with destruction proceeding in a semi-linear fashion; or insulitis and β cell destruction may occur closer to diagnosis. The latter fits the observations that (i) the proportion of infiltrated islets is modest near diagnosis, and insulitis is only present in non-diabetic donors with multiple autoantibodies (16,21,23); (ii) β cell loss near diagnosis is partial in many patients (16,21,23), and no appreciable reduction in β cell mass has been reported in autoantibody-positive donors (44,45); and (iii) impaired glucose metabolism, abnormalities of insulin secretion (46,47) and insulin sensitivity (48), and increased β cell death (49) usually manifest shortly before diagnosis in longitudinal studies of at-risk relatives.…”
Section: T Cells In the Prediabetic Pancreassupporting
confidence: 64%
“…In the Belgian Diabetes Registry, autoantibody-positive first-degree relatives with random PI/C ratios above the 66th percentile had an increased 5-year risk of T1D development [26]. Sims et al recently reported that within the TrialNet Pathway to Prevention cohort, an international cohort of autoantibody-positive family members of individuals with T1D, fasting PI/C ratios were significantly increased ~12 months prior to onset of T1D [27••]. Elevations were most pronounced in children ≤10 years, where median PI/C ratios were 3-fold higher than those who did not progress to T1D.…”
Section: Proinsulin/c-peptide Ratio As a Circulating Biomarker Of β-Cmentioning
confidence: 99%
“…Elevations were most pronounced in children ≤10 years, where median PI/C ratios were 3-fold higher than those who did not progress to T1D. However, even among the entire group, increased PI/C ratios were associated with increased odds of progression to T1D, after correction for age and BMI [27••]. …”
Section: Proinsulin/c-peptide Ratio As a Circulating Biomarker Of β-Cmentioning
confidence: 99%
“…Prevention studies mentioned above used autoantibodies as biomarkers for T1D. Other potential biomarkers of T1D development include: genetic predisposition (13, 58, 107-109), unmethylated preproinsulin (110, 111), proinsulin-to-C-peptide ratios (112, 113), and microRNA species (114). In addition, β-cell derived neo-antigens offer another potential biomarker of T1D, but also a target for T1D prevention (115, 116).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%